2012
DOI: 10.1037/a0028969
|View full text |Cite
|
Sign up to set email alerts
|

Coping with bullying at work and health related problems.

Abstract: This study investigated bullying in the workplace. More specifically, it explored the mental and physical health consequences of being bullied in the workplace and the role of coping as a moderating variable among 361 people living in the Netherlands who, at the time of the study, were employed for at least eight hours a week in an organization where they have both colleagues and a manager. Of these 361 employees, 139 (39%) reported having experienced at least one form of bullying listed in the questionnaire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 56 publications
(85 reference statements)
5
84
0
6
Order By: Relevance
“…Confirming Hypothesis 3, our data revealed that exposure to workplace bullying is positively related to emotional exhaustion. In line with previous studies indicating links between workplace bullying and burnout [38,48,49,51,53], the present study confirms that workplace bullying can contribute to burnout. Our findings have several implications.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Confirming Hypothesis 3, our data revealed that exposure to workplace bullying is positively related to emotional exhaustion. In line with previous studies indicating links between workplace bullying and burnout [38,48,49,51,53], the present study confirms that workplace bullying can contribute to burnout. Our findings have several implications.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, in line with many studies linking workplace bullying to burnout [38,49,51,53], the present study contends that workplace bullying predicts emotional exhaustion. Our third hypothesis is as follows:…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Occupational stress research suggests that bullying is a major work-related stressor (Zapf, 1999) and has a significant impact on mental and physical health (Dehue, Bolman, Völlink, & Pouwelse, 2012). It could lead to extreme feelings (learned helplessness or distress) or extreme behaviors directed toward self (suicide).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that targets of workplace bullying endured sleeplessness, depression, and anxiety (Rodríguez-Muñoz, Notepapers, & MorenoJiménez, 2011). In this hostile workspace, targets of workplace bullying recruited allies at work, and cultivated a social network to withstand the bully's hostilities (Dehue, Bolman, Völlink, & Pouwelse, 2012;Stroebe, Zech, Stroebe et al, 2005). Hence, bullying was the antecedent of pervasive stressors, often rendering the target defenseless in the wake of such abuse (Einarsen, Hoel, Zapf & Cooper, 2011).…”
Section: Introductionmentioning
confidence: 99%